Malaria Prevalence and Macroeconomic Output in Ghana, 1990 to 2019 - Mustapha Immurana PhD; Desmond Klu PhD; Matilda Aberese-Ako PhD; Ibrahim Abdullahi BA (SAGE Publishing, 2024)
In Ghana, malaria remains the number 1 reason for outpatient department visits, making it a major public health problem. Thus, there could be significant lost productivity days as a result of malaria morbidity and mortality, which could negatively affect economic output at the macrolevel. Nonetheless, there is a dearth of empirical evidence of the effect of malaria on macroeconomic output in Ghana. This study therefore aims to provide the foremost empirical evidence regarding the effect of malaria prevalence on macroeconomic output in Ghana using a time series design with data spanning the period 1990 to 2019. Gross Domestic Product (GDP), serving as a proxy for macroeconomic output, is the dependent variable, while the prevalence of malaria (overall, among only males and among only females) serves as the main independent variable. The Ordinary Least Square (OLS) regression is used as the baseline estimation technique and the Instrumental Variable Two-Stage Least Square (IV2SLS) regression is employed as the robustness check estimator due to its ability to deal with endogeneity. The IV2SLS regression results show that a percentage increase in the overall prevalence of malaria is associated with a 1.16% decrease in macroeconomic output at 1% significance level. We also find that the effect of malaria in males on macroeconomic output is slightly higher relative to females. The findings from the OLS regression are not qualitatively different from the IV2SLS regression estimates. There is therefore the need to strengthen efforts such as quality case management, larval source management, mass distribution of long-lasting insecticide-treated bed nets, social behavior change, surveillance (both epidemiological and entomological), intermittent preventive treatment of malaria in pregnancy, research among others, which are important toward eliminating malaria.